Three dimensional nanofabrication using surface forces - Cho, Jeong-Hyun (2010)
We describe strategies to curve, rotate, align and bond precisely patterned two dimensional (2D) nanoscale panels using forces derived from a minimization of surface area of liquefying or coalescing metallic grains. We demonstrate the utility of this approach by discussing variations in template size, patterns and material composition. The strategy provides a solution path to overcome the limitation of inherently two dimensional lithographic processes by transforming 2D templates into mechanically robust and precisely patterned nanoscale curved structures and polyhedra with considerable versatility in material composition.